2018
DOI: 10.1371/journal.pone.0195238
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying differences in water and carbon cycling between paddy and rainfed rice (Oryza sativa L.) by flux partitioning

Abstract: Agricultural crops play an important role in the global carbon and water cycle. Global climate change scenarios predict enhanced water scarcity and altered precipitation pattern in many parts of the world. Hence, a mechanistic understanding of water fluxes, productivity and water use efficiency of cultivated crops is of major importance, i.e. to adapt management practices. We compared water and carbon fluxes of paddy and rainfed rice by canopy scale gas exchange measurements, crop growth, daily evapotranspirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 59 publications
(70 reference statements)
3
10
0
Order By: Relevance
“…The rice paddies under both water management systems were net sinks of atmospheric C and did not differ significantly from each other in terms of NEE, GPP, RE or decomposition rates for the seasonal mean or during any of the key stages of plant growth measurement. Mean daily NEE in the CF rice paddy was −15.21 ± 0.95 g C m −2 d −1 (range:-38.87 to −0.61), and GPP 24.01 ± 1.20 g C m −2 d −1 (range: 51.07 to 4.97), affirming prior results of rice paddy studies using eddy covariance techniques in East Asia, India and the USA, where NEE estimates are between 5 and −39 and GPP between 5 and 50 g C m −2 day −1 (Alberto et al, 2009; Bhattacharyya et al, 2013; Miyata et al, 2005; Nay-Htoon et al, 2018; Saito et al, 2005; Swain et al, 2016). However, unlike in other studies where they reported a more positive NEE in intermittently flooded systems (Alberto et al, 2014; Liu et al, 2013; Miyata et al, 2000), mean daily NEE fluxes under AWD in this study were very similar to CF (−16.00 ± 1.00 g C m −2 d −1 (range: −38.39 to −0.70), and GPP 23.26 ± 1.27 g C m −2 d −1 (range: 56.46 to 4.02)), challenging our first hypothesis ( H1 ).…”
Section: Discussionsupporting
confidence: 76%
“…The rice paddies under both water management systems were net sinks of atmospheric C and did not differ significantly from each other in terms of NEE, GPP, RE or decomposition rates for the seasonal mean or during any of the key stages of plant growth measurement. Mean daily NEE in the CF rice paddy was −15.21 ± 0.95 g C m −2 d −1 (range:-38.87 to −0.61), and GPP 24.01 ± 1.20 g C m −2 d −1 (range: 51.07 to 4.97), affirming prior results of rice paddy studies using eddy covariance techniques in East Asia, India and the USA, where NEE estimates are between 5 and −39 and GPP between 5 and 50 g C m −2 day −1 (Alberto et al, 2009; Bhattacharyya et al, 2013; Miyata et al, 2005; Nay-Htoon et al, 2018; Saito et al, 2005; Swain et al, 2016). However, unlike in other studies where they reported a more positive NEE in intermittently flooded systems (Alberto et al, 2014; Liu et al, 2013; Miyata et al, 2000), mean daily NEE fluxes under AWD in this study were very similar to CF (−16.00 ± 1.00 g C m −2 d −1 (range: −38.39 to −0.70), and GPP 23.26 ± 1.27 g C m −2 d −1 (range: 56.46 to 4.02)), challenging our first hypothesis ( H1 ).…”
Section: Discussionsupporting
confidence: 76%
“…5 ). This is likely to be due to the shape and small size of rice stomata allowing fast responses ( McAusland et al , 2016 ), but also the evolutionary history of rice, which was domesticated from emergent aquatic progenitors and then bred in paddy conditions where water would not be limiting to the plant ( Nay-Htoon et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its wild ancestors were emergent aquatic plants, and most breeding programmes that target the improvement of lowland rice utilize flooded paddies, where water is not limiting. After millennia of cultivating rice in conditions with plentiful water, it is likely that rice is less conservative in its water usage, explaining the lower L S (Nay-Htoon et al, 2018).…”
Section: Photosynthetic Induction In Rice Is Limited Mostly By Biochementioning
confidence: 99%